Health-related quality of life after apalutamide treatment in patients with metastatic castration-sensitive prostate cancer (TITAN): a randomised, placebo-controlled, phase 3 study. Issue 11 (November 2019) - Agarwal, Neeraj; McQuarrie, Kelly; Bjartell, Anders; Chowdhury, Simon; Pereira de Santana Gomes, Andrea J; Chung, Byung Ha; Özgüroğlu, Mustafa; Juárez Soto, Álvaro; Merseburger, Axel S; Uemura, Hirotsugu; Ye, Dingwei; Given, Robert; et al.
Summary: Background: In the phase 3 TITAN study, the addition of apalutamide to androgen deprivation therapy (ADT) significantly improved the primary endpoints of overall survival and radiographic progression-free survival in patients with metastatic castration-sensitive prostate cancer. We aimed to assess health-related quality of life (HRQOL) in TITAN, including pain and fatigue. Methods: In this randomised, placebo-controlled, double-blind, phase 3 study, patients with metastatic castration-sensitive prostate cancer (defined as not receiving ADT at the time of metastatic disease progression) aged 18 years and older, receiving continuous ADT (selected at the investigator's discretion), and with an Eastern Cooperative Oncology Group performance status score of 0 or 1 were randomly assigned (1:1), using an interactive web response system, to receive oral apalutamide (four 60 mg tablets, once daily) or matching placebo. Previous localised disease treatment or previous docetaxel for metastatic castration-sensitive prostate cancer were allowed. Randomisation was stratified by Gleason score at diagnosis, region, and previous docetaxel treatment. Randomisation was done using randomly permuted blocks (block size of four). Investigators, research staff, sponsor study team, and patients were masked to the identities of test and control treatments. Patient-reported outcomes were prespecified exploratory endpoints and were the Brief Pain Inventory-Short Form (BPI-SF), Brief Fatigue Inventory (BFI), Functional Assessment of Cancer Therapy-Prostate (FACT-P), and EuroQoL 5D questionnaire 5 level (EQ-5D-5L). BPI and BFI were completed for 7 consecutive days (days −6 to 1 inclusive of each cycle visit), then at months 4, 8, and 12 in follow-up. FACT-P and EQ-5D-5L were completed during cycles 1–7, then every other cycle until the end of treatment, and at months 4, 8, and 12 in follow-up. Analyses were based on the intention-to-treat population. Missing patient-reported outcome assessments were calculated as the expected number of assessments for a visit minus the actual number of assessments received for that visit. For time-to-event endpoints, when median values could not be calculated because less than 50% of patients had degradation, 25th percentiles were compared. This study is registered with ClinicalTrials.gov, number NCT02489318, and is ongoing. Findings: Between Dec 9, 2015, and July 25, 2017, 1052 eligible patients were enrolled randomly assigned to apalutamide (n=525) or placebo (n=527). Data cutoff for this analysis of patient-reported outcomes was Nov 23, 2018. Median follow-up for time to pain-related endpoints ranged from 19·4 to 22·1 months. Patients were mostly asymptomatic at baseline: on the BPI-SF pain severity scale of 0–10, median pain scores (indicating worst pain in the past 24 h) were 1·14 (IQR 0–3·17) in the apalutamide group and 1·00 (0–2·86) in the placebo group, and median worst fatigue scores on the BFI were 1·29 (IQR 0–3·29) in the apalutamide group and 1·43 (0·14–3·14) in the placebo group. Patient experience of pain and fatigue (intensity and interference) did not differ between the groups for the duration of treatment. Median time to worst pain intensity progression was 19·09 months (95% CI 11·04–not reached) in the apalutamide group versus 11·99 months (8·28–18·46) in the placebo group (HR 0·89 [95% CI 0·75–1·06]; p=0·20). Median time to pain interference progression was not reached in either group (95% CI 28·58–not reached in the apalutamide group; not reached–not reached in the placebo group). 25th percentiles for time to pain interference progression were 9·17 months (5·55–11·96) in the apalutamide group and 6·24 months (4·63–7·43) in the placebo group (HR 0·90 [95% CI 0·73–1·10]; p=0·29). FACT-P total scores and EQ-5D-5L data showed preservation of HRQOL in both groups. The median time to deterioration as determined by FACT-P total score was 8·87 months (95% CI 4·70–11·10) in the apalutamide group and 9·23 months (7·39–12·91) in the placebo group (HR 1·02 [95% CI 0·85–1·22]; p=0·85). Interpretation: Apalutamide with ADT is a well-tolerated and effective option for men with metastatic castration-sensitive prostate cancer. The combination significantly improves survival outcomes compared with ADT alone while maintaining HRQOL despite additive androgen blockade. Funding: Janssen Research & Development.